2010
DOI: 10.1590/s0021-75572010000300009
|View full text |Cite
|
Sign up to set email alerts
|

Associação entre desnutrição em crianças moradoras de favelas, estado nutricional materno e fatores socioambientais

Abstract: Objective: To investigate the association of malnutrition in children living in substandard settlements (favelas) of Maceió, Brazil, with maternal nutritional status and environmental conditions. Methods:Cross-sectional study involving a probability sample of 2,075 mothers (18 to 45 years) and their children (4 months to 6 years), living in the favelas of the city of Maceió. First, we conducted a cluster analysis with the purpose of choosing the settlements and the administrative region of the city of Maceió w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
20
0
8

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 15 publications
2
20
0
8
Order By: Relevance
“…Other studies on the relation between social and environmental conditions and malnutrition in São Paulo, Belo Horizonte, Maceió and Rio Grande do Sul also showed this association [31-34]. This relationship may result from the basic information on the importance of personal and household hygiene habits and practices of adequate nutrition for child growth and development.…”
Section: Discussionmentioning
confidence: 77%
“…Other studies on the relation between social and environmental conditions and malnutrition in São Paulo, Belo Horizonte, Maceió and Rio Grande do Sul also showed this association [31-34]. This relationship may result from the basic information on the importance of personal and household hygiene habits and practices of adequate nutrition for child growth and development.…”
Section: Discussionmentioning
confidence: 77%
“…Although the reduction in malnutrition and underweight can be justified by the improved life conditions, the higher coverage of health, and the reduced fecundity, the evolution of excess weight was mainly caused by urbanization and its impact on dietary patterns and physical activities 23 . A study conducted by Silveira et al 21 found the prevalence of overweight and obesity in 11.3% of the residents of slums in Maceió. A study by Silva 9 , including 32,351 children aged from 5 to 10 years old, PBF beneficiaries in the state of Sergipe, 2010, found the prevalence of overweight to be 13.1% among girls and 13.3% among boys, and the prevalence of obesity to be 11.2% among girls and 14.5% among boys; in this study, the prevalence of overweight was 14.8% among girls and 16.1% among boys.…”
Section: Discussionmentioning
confidence: 98%
“…In Maceió (Alagoas), a study conducted among children (aged from 4 months to 6 years old), living in slums showed the prevalence of moderate and severe malnutrition to be 8.6% 21 . The Ministry of Health assessed the nourishment program with a sample composed of four cities in the Northeast, and the prevalence of underweight/height was 16.6% 22 .…”
Section: Discussionmentioning
confidence: 99%
“…Os dados de desnutrição infantil observados foram superiores aos encontrados por Silveira et al (2010) ao avaliarem também crianças moradoras de favelas de Maceió, os quais encontraram uma prevalência de baixa estatura de 8,6%, e por Ferreira e Luciano (2010) que estudaram uma amostra probabilística da cidade de Maceió e do Estado de Alagoas e encontraram em crianças uma prevalência de déficit estatural de 6,2% e 10,4%, respectivamente. Os adolescentes também apresentaram uma alta taxa de desnutrição (20%).…”
Section: Discussionunclassified